Demographic changes and asset prices in an overlappig generations model - Beatrice D. Simo-Kengne; Frank Riedel; Ghislain-Herman Demeze-Jouatsa (Bielefeld University, Center for Mathematical Economics (IMW), 2022)
We examine the effect of demographic shifts on asset prices in an overlapping generations model with endogenous population dynamics. We establish a robust inverse relationship between returns and the old dependency ratio. We document the absence of a simple monotonic relationship between asset prices and demographic parameters. Returns depend on the joint evolution of fertility, mortality, and lifetime work in a complex way that we quantify. We carry out an extensive empirical study involving 55 countries. Both theoretical and empirical findings reconcile existing propositions on the population age structure and asset returns for riskless and short-lived risky assets.
urn:nbn:de:0070-pub-29675851
Keywords: D9; E44; 330; Demography; Asset prices; OLG; Panel cointegration; Granger causality